Cyfrowe strategie badań i edukacji humanistycznej - Dziak, Aleksandra (Postscriptum Polonistyczne, 2020)
The following issues are being discussed in the article: digital tools in humanistic research, the methodology of online research and the specific character of research on the Internet, tools of informative technology in Polonistic university education (methodology of online teaching), psychological and pedagogical aspects of university elearning (educational strategies used in distant learning).